IMPACT OF SOME CYTOKINES TO EFFICIENCY OF INFERTILITY TREATMENT BY MEANS OF IN VITRO FERTILIZATION - N. O. Motovilova; I. Yu. Kogan; K. A. Syssoev; A. N. Buinova; A. Yu. Griaznov; Areg A. Totolyan (Медицинская иммунология, 2014)
Abstract. Present study defines clinical, hormonal and immunological factors allowing to predict outcomes of IVF cycles in patients with combined forms of infertility at their reproductive age. Indices of gonadotrophic ovarian stimulation in IVF cycles in patients of reproductive age with combined forms of infertility depend on their age and cytokine contents in follicular fluid. Effectiveness of gonadotropin-induced ovarian stimulation is inversely dependent on the patients’ age, its increase is related to increased contents of pro-inflammatory cytokines in follicular fluid and increased expression of CCR1, along with decreased expression of CCR3 chemokine receptors in endometrium. Effectiveness of gonadotropin-induced ovarian stimulation depends on concentration of cytokines in the follicular fluid, which is argued by presence of a significant direct correlation between the number of growing follicles, oocytes and local contents of IL-10, IL-15, eotaxin, MIP-1β, RANTES, TNFα, IFNγ, and GMCSF. Free testosterone levels show a positive correlation with numbers of oocytes obtained from the ovarian punctate, and CXCR2 and CCR3 expression in endometrium, as well as a negative correlation was found with IL-4 contents in follicular fluid. In patients with negative IVF cycle outcomes, levels of IL-13 in follicular fluid upon ovarian stimulation proved to be twofold higher than those in patients with successful pregnancy after IVF. Prognosis for pregnancy in a cycle of treatment in patients with combined forms of infertility of reproductive age is determined by a patients’ story, and a variety of clinical, hormonal and embryological factors which can increase predictive accuracy of the IVF outcomes. To determine a probability of successful pregnancy after IVF cycle, an appropriate prognostic index is recommended, with a sensitivity levels of 93% and specificity of 89%.